Evaluasi Anggaran Biaya menggunakan Batu Bata Merah dan Batu Bata Ringan Gedung Kantor Kelurahan Bareng Kecamatan Klaten Tengah Kabupaten Klaten - Sari, Sely Novita (Universitas Islam Balitar Blitar, 2019)
Light brick is an alternative to making walls in addition to the red brick series used by ordinary people. The purpose of this study is to compare the calculation of budget costs and the need to use red brick walls with light brick walls. The implementation method is to calculate the unit price analysis of the installation of red brick and light brick, the AHS is multiplied by the volume and the RAB is obtained, then the calculated RAB is compared between the two. Conclusion the price of installing a red brick wall pair is Rp. 44,128,086.00. The price of installing a lightweight brick wall pair is Rp. 85,295,824.71. The difference between the two jobs is Rp. 41,167,738.71. The percentage difference between the two jobs is 48.3%.